Islamic Religious and Character Education (IRCE) Based on Education for Sustainable Development (ESD) in Palm Oil Plantation Environment - Dharma, Kukuh Budhi; Zuhriyah, Lailatul; Arifah, A'isatul (Proceeding International Conference on Education, 2025)
This study investigates the implementation of Islamic Religious and Character Education (IRCE) integrated with Education for Sustainable Development (ESD) principles in SMP Swasta Sumbermas Sarana PT Tanjung Sawit Abadi, Lamandau, Central Kalimantan. The research addresses the critical need for bridging Islamic environmental theology with practical environmental education in palm oil plantation communities. Using a qualitative case study approach, data were collected through semi-structured interviews with 15 participants, focus group discussions with 60 students, classroom observations, and document analysis over six months. The study explores IRCE-ESD integration through three mechanisms: conceptual alignment, pedagogical innovation, and community engagement. Results demonstrate significant enhancement of students' environmental awareness with large effect sizes (Cohen's d = 2.67-3.42), achieving 78% improvement in environmental knowledge and 92% successful integration of ESD objectives within Islamic frameworks. Key success factors include teacher professional development (89% confidence improvement), community engagement (transforming 25% skepticism to 82% support), and curriculum adaptation incorporating khalifah fil ardh concepts. Implementation challenges included resource limitations and teacher preparedness gaps, addressed through collaborative material development and intensive training. Behavioral outcomes showed dramatic increases in environmental participation from 23% to 89%, sustained over six months. Students developed integrated Islamic-environmental identity, articulating connections between religious obligations and environmental responsibility. This research contributes empirical evidence for religiously informed environmental education effectiveness and provides a replicable framework for integrating sustainability within religious education contexts, supporting broader IRCE-ESD implementation in Muslim-majority communities.